Frequency of Anaplasma sp. and Ehrlichia sp. in dogs with symptoms compatible with hemoparasitic disease in Huánuco, Peru - Tasayco Alcántara, Walter Richard (2021)
The study aimed to determine frequency of Anaplasma sp. y Ehrlichia sp. in domestic canines with compatible symptoms with hemoparasitic disease of veterinary centers of the Huánuco, Amarilis y Pilcomarca districts. For this, it was selected intentionally to 100 dogs, from whom blood samples are drawn to perform haematological analysis and double immunochromatographic test for antibody detection of Anaplasma and Ehrlichia; in addition to applying a epidemiological questionnaire to the owners. The study was conducted between the months of may and october 2020. The 61% was positive to Anaplasma, the 85% to Ehrlichia, and in the 55% (55/100) of the dogs existed coinfection with both pathogens. The haemogram of the positive dogs Anaplasma y Ehrlichia presented anemia, leucopenia and thrombocytopenia like the most frequent clinical signs. Association found between the positive results to Ehrlichia and the race variable, thrombocytopenia, and the clinic sign of pale mucous membranes in the dogs (p<0.05). The findings found from this study show a high frequency of Ehrlichia sp., is confirmed for the first time coinfection Anaplasma sp. + Ehrlichia sp. in Huánuco.